2023
DOI: 10.3389/fendo.2023.1205846
|View full text |Cite
|
Sign up to set email alerts
|

The gut-retina axis: a new perspective in the prevention and treatment of diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a microvascular lesion that occurs as a complication of diabetes mellitus. Many studies reveal that retinal neurodegeneration occurs early in its pathogenesis, and abnormal retinal function can occur in patients without any signs of microvascular abnormalities. The gut microbiota is a large, diverse colony of microorganisms that colonize the human intestine. Studies indicated that the gut microbiota is involved in the pathophysiological processes of DR and plays an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…The pathobiological processes contributing to the development of diabetic retinopathy (DR) are multifaceted and involve intricate cellular and molecular mechanisms. These mechanisms encompass hyperglycemia-triggered oxidative stress, inflammation, PKC pathways, microbiota alterations, and imbalances in HSPCs [31][32][33]. Among these, NOD-like receptors (NLRs), including NOD1, NLRP1, and NLRP3, serve as vital interfaces between microbiota and systemic chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The pathobiological processes contributing to the development of diabetic retinopathy (DR) are multifaceted and involve intricate cellular and molecular mechanisms. These mechanisms encompass hyperglycemia-triggered oxidative stress, inflammation, PKC pathways, microbiota alterations, and imbalances in HSPCs [31][32][33]. Among these, NOD-like receptors (NLRs), including NOD1, NLRP1, and NLRP3, serve as vital interfaces between microbiota and systemic chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the interaction between the ocular and intestinal microbiota have increased in recent years. Some researchers hypothesize the existence of a gut-eye "axis": the alteration of the intestinal microbiota seems to be linked to some eye diseases, including uveitis, macular degeneration, and glaucoma [179][180][181][182]. Most microorganisms are located in the intestine, especially in the ascending colon: therefore, we can find bacteria, fungi, viruses, and helminths in constant symbiotic relationship with our immune system and with numerous functions, such as metabolic, protective, of immune education, and of vitamin production [183].…”
Section: Gut-eye Axismentioning
confidence: 99%
“…Currently, numerous studies have demonstrated a connection between the metabolism of intestinal microorganisms and retinal diseases, so the concept of the gut-retinal axis has been proposed by scholars ( 7 ). The gut microbiota has been found to influence the expansion of various retinal disorders, including diabetic retinopathy, optic neuritis, age-related macular degeneration, and retinopathy of prematurity.…”
Section: Introductionmentioning
confidence: 99%